Feline obesity causes hematological and biochemical changes and oxidative stress – a pilot study - Martins, Tainara de Oliveira; Ramos, Rebecca Cápera; Possidonio, Geovana; Bosculo, Maria Rachel Melo; Oliveira, Paula Lima [UNESP]; Costa, Leticia Ramos; Zamboni, Vinicius Aquiles Gomes; Marques, Marcel Gambin; de Almeida, Breno Fernando Martins [UNESP] (Springer Nature, 2022)
Obesity, an extremely important factor in feline clinical practice, is estimated to affect up to one third of the feline population. Moreover, it can trigger chronic inflammation, which could predispose to oxidative stress by increasing reactive oxygen species, thereby generating potentially irreversible cellular damage. This study analyzed hematological, biochemical and oxidative stress profiles at various degrees of feline obesity. Forty-five cats were selected and divided into three groups: control (n = 17), overweight (n = 13) and obese (n = 15), after clinical and laboratory evaluation and body condition score. Biochemical and oxidative stress analyses were performed using a photocolorimeter and hematological analyses were performed in a veterinary cell counter. Obese cats showed increased mean corpuscular volume (MCV), red cell distribution width (RDW), HDL cholesterol and triglycerides and decreased activity of gamma-glutamyl transferase (GGT) than control cats, although within the reference ranges for the species. As for oxidative stress, obese cats showed higher total antioxidant capacity (TAC), by the inhibition of 2,2’-Azino-Bis-3-Ethylbenzthiazoline-6-Sulfonic Acid (ABTS), inhibition of ABTS associated with horseradish peroxidase (ABTS + HRP), cupric ion reducing antioxidant capacity (CUPRAC) and ferric reducing antioxidant power (FRAP) methods, while overweight cats had a higher TAC-ABTS + HRP and TAC-FRAP than control cats. We conclude that the conditions of natural obesity and overweight in the feline species alter its hematological, biochemical and oxidative stress parameters.
Keywords: Antioxidants; Cats; Complete blood count (CBC); Reactive oxygen species